2017
DOI: 10.2147/cwcmr.s101323
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation therapy to promote healing of chronic wounds: a review of reviews

Abstract: Purpose:The overall objective of this study is to identify and appraise all of the existing clinical research literature that has evaluated the effect of electrical stimulation therapy (EST) on wound healing outcomes in adults with various types of chronic wounds. Methods: A systematic and comprehensive search of four electronic databases and gray literature was carried out, and references included in related review articles were checked. Prospective and controlled clinical trials, systematic reviews (SRs), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…The authors of the available SRs on effectiveness of electrical stimulation therapy (EST) in VLU management concluded that there is evidence that electrotherapy could be effective. However, the authors warn that some of the included studies were of low quality; moreover, the described interventions focused on all types of chronic wounds …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the available SRs on effectiveness of electrical stimulation therapy (EST) in VLU management concluded that there is evidence that electrotherapy could be effective. However, the authors warn that some of the included studies were of low quality; moreover, the described interventions focused on all types of chronic wounds …”
Section: Resultsmentioning
confidence: 99%
“…Properly designed RCTs will need to include well‐defined outcomes that are consistent with other studies and are valid measures of VLU treatment . Primary outcomes must focus on time to heal of the target ulcer, although information on ulcer size and rate of healing will be useful as a closely related secondary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Houghton (2017) found that electrical stimulation therapy (EST), where electrodes are placed on or around the wound and an electric current supplied to the area, stimulates tissue repair and wound closure in chronic wounds. While EST is understood to activate the nerves and muscles of the wound bed, the scientific process of EST is not fully understood.…”
Section: Electrical Stimulationmentioning
confidence: 99%
“…While EST is understood to activate the nerves and muscles of the wound bed, the scientific process of EST is not fully understood. EST can be expensive; therefore, diagnostic processes identified in table 2 should be considered first before the prescription of EST (Houghton, 2017).…”
Section: Electrical Stimulationmentioning
confidence: 99%
“…2,3 Decades of investigation have examined the role of electrical stimulation in enhancing wound healing, particularly for skin and bone in animal models and clinical trials. [4][5][6] The field of bioelectricity has highlighted our understanding of the diverse and profound responses of cells to EF application upon which to build our regenerative strategies.…”
Section: Introductionmentioning
confidence: 99%